Pembuatan Hidrogel Berbasis Carboxymethyl Cellulose (CMC) dan Pektin sebagai Adsorben Logam Cu dengan Metode Freeze-Thaw - Dewi, Nurazizah Melani; Maelan, Nabilla Maharani; Andini, Sri; Perdani, Meka Saima; Wahyuningtyas, Aulia (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
Water pollution is a serious global problem caused by increasing industrialization and urbanization. The heavy metal Cu is one of the dangerous compounds that causes water pollution because it has a toxic effect on humans and can cause mental retardation, anemia, hypertension, etc. Removal of Cu metal in water can be done using CMC and Pectin-based hydrogel adsorbents. Hydrogels are hydrophilic polymer composites with a physically well-defined three-dimensional (3D) network and chemically responsive functional groups, which enable the hydrogel to easily capture metal ions without dissolving. The hydrogel synthesized via the Freeze-Thaw method has greater elastic characteristics. The adsorption properties were investigated by two isotherm models and five kinetic models. FTIR analysis proved that the â€“OH group was detected freely due to the interaction between CMC and pectin, the COOH group with the highest ability to bind metals, and other groups, namely C=O, C-O, and C-O-C. BET analysis shows that the hydrogel has a surface area of 1.685 mÂ²/g and is classified as type 1 on the isotherm chart, referring to the dominance of micropores in a material or materials with mesopore content close to micropores. The optimum conditions in the adsorption process are at a concentration of 223 ppm, using the Langmuir isotherm model with an adsorption efficiency of 20,84%. The highest adsorption capacity was at a concentration of 74 ppm which occurred at 120 minutes, using a Pseudo 2nd Order kinetic model with an adsorption efficiency of 85,07%.